Author Correction: Genetic polymorphisms of lncRNA-p53 regulatory network genes are associated with concurrent chemoradiotherapy toxicities and efficacy in nasopharyngeal carcinoma patients. Issue 1 (December 2017) - Wang, Youhong; Guo, Zhen; Zhao, Yu; Jin, Yi; An, Liang; Wu, Bin; Liu, Zhaoqian; Chen, Xiaoping; Chen, Xiang; Zhou, Honghao; Wang, Hui; Zhang, Wei
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.